Empowering A Strong Brand Awareness of Burayot Si Madu Through Social Media Marketing - Syafei, M. Yani; Narimawati, Umi; Susilawati, Erna; Wardhani, Kristina (MOVE: Journal of Community Service and Engagement, 2025)
This Community Service activity is not only aimed at making "Burayot" as a traditional food from Garut better known by the wider community but also to increase the knowledge of the owners and employees of the Burayot Si Madu UMKM regarding strengthening Brand awareness through the use of social media marketing, especially Instagram. If this brand awareness is embedded in the minds of customers, it will be easier to increase product sales. The method in this Community Service activity is carried out through mentoring and sharing sessions. The final result of this Community Service activity is expected to be able to increase engagement from Burayot Si Madu Instagram followers by providing mentoring on the above theme through increasing followers who comment, like and share on each post from Burayot Si Madu, so that the product is better known by the public and can increase product sales.